Analyzing Students’ difficulties in learning to write - Mundi, Theresia; Mutaat; Radik, Darmawan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
The study aims to identify the students’ perception of learning writing in the literature college. The method applied in the study was quantitative. The number of participants recruited purposively was 40 students. The findings indicated that, despite being considered necessary, most of the students perceived that writing belongs to the most challenging subject. The participants also perceived that learning from the newspaper could provide the most current news to the participants. Lastly, in terms of writing sources, they still considered that the learning sources provided by the teachers were essential for them. However, they also expected that they could learn from other sites, such as social media, as this media could provide them with the most current sources in writing and more flexible and exciting sources.